2009
DOI: 10.1017/s0008423909990060
|View full text |Cite
|
Sign up to set email alerts
|

The Origins of Political Attitudes and Behaviours: An Analysis Using Twins

Abstract: Abstract.This article provides a behaviour genetic heritability analysis of several political issues, including social and economic conservatism, general interest in politics, attitudes toward the major Canadian federal parties, federal party identification and national vote choice. Substantial genetic effects were found for four of six political attitude scales, with heritability values ranging from 41 per cent to 73 per cent. Genetic effects are also reported for several individual items (including feelings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
45
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(56 citation statements)
references
References 55 publications
9
45
1
1
Order By: Relevance
“…Alford et al (2005, and Bell et al (2009) did not report DZOS correlations. In Hatemi and colleagues' (2007) Australian twin study of voting behavior, the authors found "some substantial differences in the correlations of opposite sex [DZ] pairs compared to those for the same sex DZ pairs" (p. 442).…”
Section: Testing the Validity Of The Eeamentioning
confidence: 88%
See 2 more Smart Citations
“…Alford et al (2005, and Bell et al (2009) did not report DZOS correlations. In Hatemi and colleagues' (2007) Australian twin study of voting behavior, the authors found "some substantial differences in the correlations of opposite sex [DZ] pairs compared to those for the same sex DZ pairs" (p. 442).…”
Section: Testing the Validity Of The Eeamentioning
confidence: 88%
“…Most twin researchers in political science use the trait-relevant defi nition of the EEA (Bell et al, 2009, did not discuss the EEA). According to Medland and Hatemi (2009), one of the two "central questions of the equal environment assumption (EEA)" is "whether these differences [between MZs and DZs] infl uence the specifi c trait under analysis" (pp.…”
Section: The Two Main Definitions Of the Eeamentioning
confidence: 99%
See 1 more Smart Citation
“…Building from earlier studies by Martin et al (1986) and Eaves, Eysenck, and Martin (1989; see also Eaves and Eysenck 1974), they found that approximately half the population variance in a summative measure of political attitudes, the Wilson-Patterson Index, could be attributable to broad-scale heritability; only 11% was attributed to the twins' shared environment, with the rest owing to unshared environment. A rapidly evolving literature on the heritability of political attitudes and behavior has since emerged, and a variety of different samples, methods, and attitudinal and/or behavioral dependent variables has largely confirmed and extended these findings (e.g., Hatemi et al 2007Hatemi et al , 2010Bell, Shermer, and Vernon 2009;Eaves and Hatemi 2008;Klemmensen et al 2010).…”
mentioning
confidence: 99%
“…Since October 2016 there have been no school in the anglophone regions of Cameroon due to student protest and constant clashes with the police (Fomunyam, 2017). Smith et al (2012), Bell et al (2009) and Hatemi and McDermott (2012a) argue that behavioural genetics has scientifically proven that political ideologies, and political or attitudinal orientation are inherited. Smith et al (2012) further note that, while no specific gene for a preference or ideological orientation exists, biological systems built by genes play an important role in mediating political attitudes.…”
Section: West and Central Africamentioning
confidence: 99%